Variation in visiting and isolation policies in neonatal units: a UK nationwide survey - Tan, Shin; Clarkson, Martin; Sharkey, Don (Lippincott, Williams & Wilkins, 2017)
Global pandemics, such as H1N1, are a major risk for neonatal patients. We surveyed UK tertiary and district neonatal units about visiting and infection control policies relating to viral respiratory infections. There was marked variation with visiting policies, tertiary units being more restrictive. Isolation, screening and outbreak management of infected babies was highly variable posing a risk in future pandemics.